Additive manufacturing with secondary processing of curve-face gears - Lin, Chao; Fan, Yu; Zhang, Zhengwen; Fu, Guang; Cao, Xijun (International journal of advanced manufacturing technology, 2016)
In order to process curve-face gears with less material, simpler processes, and high profile accuracy, a method was proposed that uses additive manufacturing (AM) as the primary process, while computer numerical control (CNC) as the secondary process, i.e., obtaining the blanks of the curve-face gear pairs using additive manufacturing and then conducting secondary processing using five-axis CNC machining. The tooth profile coordinate system of the tool, the processing coordinate system of the curve-face gear, the model of rounded corner in addendum angle, the CNC machining model, and the rapid prototyping model were established by applying space gear meshing theory, five-axis CNC machining principles, and fundamental theories in additive manufacturing. The tool’s tooth profile equation, the coordinate transformation matrix from the tooth surface of the non-circular gear to that of the curve-face gear, the fillet surface equation, the five-axis motion equation during machining, and the coordinate transformation matrix during additive manufacturing were derived. The curve-face gear pair was machined by additive manufacturing with secondary CNC processing. Tooth surface measurement of the obtained gear pair was conducted. The results show that while materials wastage and number of processes involved are largely reduced, the tooth surface precision of additively manufactured gear pairs is significantly improved. The design for curve-face gear pairs and the method of additive manufacturing with secondary processing of curve-face gears were proved to be effective.